2022
DOI: 10.1029/2022jf006590
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Role of Compaction in the Three‐Dimensional Evolution of Depositional Environments

Abstract: Coastal landscapes like coastal plains and river deltas are complex and dynamic depositional environments. They were formed over the last centuries to millennia by the deposition of inorganic and organic sediments transported seaward by rivers and delivered by flooding or produced by the decomposition of the local vegetation (Milliman & Farnsworth, 2011;Mudd et al., 2009). These dynamic environments are widespread around the world and play important socio-economic and ecological roles. They host industrial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Thus, modeling abilities are most limited when it comes to processes on a delta scale, namely accelerated subsidence and sedimentation dynamics. There are successful examples for how those processes can be modelled for management or research applications 28,193 , but efforts are needed to develop modeling frameworks that are generalizable and modular to account for delta-specific differences in data and resource availability. Secondly, new models that integrate biotic and abiotic delta and basin processes are needed to represent the fate of deltas in decision making frameworks and for sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, modeling abilities are most limited when it comes to processes on a delta scale, namely accelerated subsidence and sedimentation dynamics. There are successful examples for how those processes can be modelled for management or research applications 28,193 , but efforts are needed to develop modeling frameworks that are generalizable and modular to account for delta-specific differences in data and resource availability. Secondly, new models that integrate biotic and abiotic delta and basin processes are needed to represent the fate of deltas in decision making frameworks and for sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to what is described above for subsidence, even simple back-of-theenvelope calculations can yield some insights into how different levels of sediment splaying can contribute to aggregation 24,26,192 . One important process that all above mentioned models lack is post-depositional compaction of newly deposited sediments, a relevant 18 aspect which is only recently included in fully coupled 3D geo-mechanical models 193 . As discussed above for fluvial sediment transport, the accuracy of full-complexity, three-dimensional delta evolution models entails significant computational and data needs and specialized skills.…”
Section: Delta-scale Processes and Nature-based Solutionsmentioning
confidence: 99%
“…This near surface bed lowering is continuously replenished by new marsh accretion and therefore does not contribute much to the long‐term generation of accommodation space, as σ s accounts for only about one quarter of RSLR b below a channel depth (Figure 7b). Field (van Asselen, 2011) and modeling (Kim et al., 2010; Liang et al., 2016; Moodie & Passalacqua, 2021; Xotta et al., 2022) studies have repeatedly shown the potential influence of subsidence on surface morphology and kinematics by causing differential compaction and steering channels. However, the treatment experiment, along with notable examples from field‐scale deltas (e.g., Keogh, 2020; Steckler et al., 2022), suggest that compactional subsidence is often too shallow to significantly impact surface processes in this way.…”
Section: Discussionmentioning
confidence: 99%
“…The 2D simulator (Zoccarato & Teatini, 2017) is expanded to a 3D spatial domain, i.e. NATSUB3D (Xotta et al, 2022). The 1D compaction module is coupled to a 3D groundwater flow module and the finite element code can generate a 3D tetrahedral grid that deforms over time with sediment compaction.…”
Section: Advances In Modelling Of Natural Compactionmentioning
confidence: 99%